Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1186/s13073-020-00760-3
|View full text |Cite
|
Sign up to set email alerts
|

ASXL3 bridges BRD4 to BAP1 complex and governs enhancer activity in small cell lung cancer

Abstract: Background: Small cell lung cancer (SCLC) is a more aggressive subtype of lung cancer that often results in rapid tumor growth, early metastasis, and acquired therapeutic resistance. Consequently, such phenotypical characteristics of SCLC set limitations on viable procedural options, making it difficult to develop both screenings and effective treatments. In this study, we examine a novel mechanistic insight in SCLC cells that could potentially provide a more sensitive therapeutic alternative for SCLC patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 66 publications
2
53
2
Order By: Relevance
“…Previous study confirmed that BRD4, whose effect was found up-regulated in PA, could regulate the growth of PA tumor in mice [ 30 , 31 ], and therefore, we chose BRD4 for further analysis in the current study. BRD4 has been widely reported to be involved in the development of various cancer types, including multiple myeloma [ 32 ], small cell lung cancer [ 33 ], and ovrican cancer [ 34 ]. The expression of BRD4 could notably affect multiple biological characteristics via different approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study confirmed that BRD4, whose effect was found up-regulated in PA, could regulate the growth of PA tumor in mice [ 30 , 31 ], and therefore, we chose BRD4 for further analysis in the current study. BRD4 has been widely reported to be involved in the development of various cancer types, including multiple myeloma [ 32 ], small cell lung cancer [ 33 ], and ovrican cancer [ 34 ]. The expression of BRD4 could notably affect multiple biological characteristics via different approaches.…”
Section: Discussionmentioning
confidence: 99%
“…These results from patients suggested a critical function of ASXL3 in neuronal development, differentiation, and function. Indeed, in our recent studies, we demonstrated that in comparison to ASXL1/2, ASXL3 is a more tissue-specific additional sex combs-like protein that is essential for BRD4-dependent enhancer activation in neuroendocrine cancer 16 .…”
Section: Bap1 Complex’s Function In the Developmentmentioning
confidence: 92%
“…Interestingly, different from ASXL1 and ASXL2, which are both expressed at a bulk level across most of the cell lines, the expression of ASXL3 is more tissue-specific and shown to be strongly enriched in neuroendocrine cell lines such as human small cell lung cancer cells (Fig. 1D ) 16 . This result suggests that there is a distinctive function in the chromatin localization among BAP1–ASXL1/ASXL2/ASXL3 complexes.…”
Section: Compositions Of the Bap1 Complexmentioning
confidence: 98%
“…The most extensively characterised and evolutionary conserved of these DUBs is BAP1, which interacts with ASXL proteins to form the Polycomb Repressive Deubiquitinase complex (PR-DUB) (Scheuermann et al 2010; Wu et al 2015; Sahtoe et al 2016; Kloet et al 2016; Hauri et al 2016; Campagne et al 2019). Previous attempts to understand how BAP1 regulates gene expression and whether this relies on its H2AK119ub1 deubiquitylase activity have primarily focused on examining how the PR-DUB complex is targeted to gene promoters and distal regulatory elements, and how this regulates binding and/or activity of chromatin-modifying transcriptional co-activators (Li et al 2017b; Wang et al 2018; Campagne et al 2019; Kuznetsov et al 2019; Kolovos et al 2020; Szczepanski et al 2020). While this has revealed that BAP1 can remove H2AK119ub1 at specific loci, its primary site of action in the genome and the mechanisms by which it controls gene expression have appeared to be context-dependent and in some cases difficult to reconcile with the known roles of H2AK119ub1 in gene regulation.…”
Section: Introductionmentioning
confidence: 99%